THE ASSOCIATION BETWEEN BODY MASS INDEX AND VISCERAL FAT AREA WITH CARDIOMETABOLIC RISK STRATIFICATION IN THE INDUSTRIAL WORKERS : BODY MASS INDEX AND VISCERAL FAT - Tamio Papilika; Muhammad Mulyadi; Eko Oktafiandry (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2026)
Background: Body mass index (BMI) is widely used in occupational health screening but does not account for fat distribution and may misclassify metabolic risk. Visceral fat area (VFA) may provide additional insight into cardiometabolic risk, particularly in physically active industrial populations. This study aimed to evaluate the comparative association of BMI and VFA with cardiometabolic abnormalities and to assess whether VFA improves risk stratification in an industrial workforce. Methods: A cross-sectional study was conducted among 108 industrial workers undergoing occupational health surveillance. Body composition was assessed using bioelectrical impedance analysis. Cardiometabolic abnormality was defined as ≥1 of the following: elevated blood pressure, hypertriglyceridemia, low HDL cholesterol, dysglycemia, or corresponding medication use. BMI was categorized using Asian-Pacific cutoffs (≥23 kg/m²), and VFA as high (≥100 cm²). Associations were analyzed using chi-square tests and multivariable logistic regression adjusted for age and sex. Sensitivity analysis was performed within a ±30-day measurement interval. Results: Among workers with BMI ≥23 kg/m², those with high VFA had a significantly higher prevalence of cardiometabolic abnormalities (82.5% vs. 48.9%, p<0.001). High VFA was independently associated with increased odds of abnormality (OR 6.66, 95% CI 2.30–19.31, p<0.001), whereas BMI was not independently associated. Results remained consistent in sensitivity analysis. Conclusion: VFA improves cardiometabolic risk stratification beyond BMI and provides a more actionable basis for fitness-for-work assessment in industrial settings.